Wayward categorial shift: so odd an article. (May 2019) - Van de Velde, Freek
Abstract: This article presents a diachronic study of the so-called 'Big Mess Construction', whereby an adverb of degree and an adjective precede an article, as in English so good a bargain . Due to the challenges this construction poses to noun phrase syntax, it has been the subject of a number of scholarly studies, often yielding ingenious explanations for its unusual syntactic behavior. Against most of these accounts, it is argued here that the construction at issue is the result of a 'historical mistake', in that inflectional morphology was reanalyzed as an indefinite article. This reanalysis, rather than the semantic nature of the adjective phrase, is the main motivation for its peculiar word order. On the theoretical side, the rise of the Big Mess Construction supports the idea that language users often look for 'local' solutions that are in accordance with the structural environment, which may result in haphazard diachronic changes. These changes may result in categorial shifts, where a form shifts from one class to another, testifying to the idea that categories are blurry. Highlights: The Big Mess Construction ('so big a mess') is a notoriously problematic construction. A closer look at its diachronic origin clarifies its inner syntax. The construction finds its origins in the reanalysis of an indefinite article. The development highlights the role of the syntactic environment on the constraints of this construction. Speakers look for local solutions